Silviculture Options for Use in Ranges Designated for the Conservation of Mountain Caribou Habitat in British Columbia - Hamilton, Dennis (Milt) (Canadian Institute for Studies in Publishing Press, 2011)
This review and synthesis of silviculture practices was conducted to identify options that could be used in managing forest stands in and adjacent to ranges designated for the protection and conservation of mountain caribou in British Columbia. The characterization of mountain caribou habitat, silviculture options, and guiding principles are intended to promote silviculture planning and practices to support, and possibly accelerate, the return of suitable habitat conditions needed to assist with mountain caribou habitat and population recovery.